Flap of the sternocephalicus muscle in the repair of a partial defect in the trachea of a rabbit (Oryctolagus cuniculus) - Fernandes, Gustavo [UNESP]; Rein, Ariadne [UNESP]; Montanhim, Gabriel Luiz [UNESP]; da Costa, Marcelo Carrijo [UNESP]; Leite, Marcella Dall’Agnol [UNESP]; Soares, Nicolle Pereira; Moraes, Paola Castro [UNESP] (FapUNIFESP (SciELO), 2024)
Purpose: The current study aimed at evaluating the repair of a partial defect of the trachea with a muscle flap, an advanced technique that employs combined suture patterns. Methods: Sixteen healthy male New Zealand white rabbits were used as an experimental model. A partial defect in the trachea within the ventral region of the fourth to eighth tracheal ring was created. Subsequently, repair was initiated with a flap of the sternocephalicus muscle. The animals were divided into four groups for postoperative evaluation using clinical, tracheoscopic, and histopathological analyses. Each group was separated according to the time of euthanasia, programmed at interval of seven (G7), 15 (G15), 30 (G30), and 60 days (G60). Results: One animal from the G60 group died, whereas the other animals had good surgical recovery without serious changes in the breathing pattern. The major clinical signs observed were stridor and coughing. Tracheoscopy revealed secretions in the tracheal lumen, exuberant granulation, and stenosis. Histopathological analysis showed growth of the ciliary respiratory epithelium at the flap site 30 days after implantation. Conclusion: Partial repair showed satisfactory results owing to the anatomical location of the muscle, adequate vascular support, and structural and physiological maintenance without serious changes in the respiratory system.
Keywords: Endoscopy; General Surgery; Respiratory System; Surgical Flaps